Penerapan Metode AHP Dan Promethee Untuk Seleksi Siswa Penerima Beasiswa Bantuan Biaya Komite Sekolah - Pandiangan, Ida Mayanju; Mesran, M; Fadlina, F (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The selection of scholarship recipients must go through careful consideration. Therefore, SPK is needed in overcoming these problems by applying the AHP and PROMETHEE methods. SPK is able to overcome this problem for the selection of scholarship recipients so that the resulting data is more effective and optimal Based on the criteria that have been determined, a student named Radit Pratama with a final score of 0.466 ranks as the student with the highest ranking score for granting aid scholarships.